KOMPENSASI, IKLIM ORGANISASI, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL KARYAWAN PONDOK PESANTREN DI KECAMATAN LENEK - Khaer, Muhammad Hizbi; Mulyono, Sugeng; Suswati, Endang; Sulaiman, Sulaiman (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
This study was meant 1) to determine the partial influence of compensation, organizational climate and motivation on Employee Organizational Commitment in Islamic Boarding Schools in Lenek District, East Lombok Regency. 2) to find out whether the variables Compensation, Organizational Climate, and Work Motivation simultaneously influence the Employee Organizational Commitment in Islamic Boarding Schools in Lenek District, East Lombok Regency. 3) to find out among the variables Compensation, Organizational Climate, and Motivation, which variable had the most dominant influence on the Employee Organizational Commitment in Islamic Boarding Schools in Lenek District, East Lombok Regency. This study was a causal associative research. This study was also a population study where the number of respondents who returned the questionnaire was 80 respondents. Quantitative analysis technique was used in this study with the assistance of the SPSS 20. It showed that 1) Compensation had a positive influence on the employee organizational commitment at Islamic Boarding School, Lenek District. East Lombok. 2) Organizational climate had a positive influence on the employee organizational commitment at Islamic Boarding School, Lenek District. East Lombok. 3) Motivation had a positive influence on the employee organizational commitment at the Islamic Boarding School, Lenek Regency East Lombok. 4) Compensation, Organizational Climate and Motivation had simultaneously a significant effect on Employee Organizational Commitment at Islamic Boarding School, Lenek District. East Lombok. 5) Among the three independent variables, Compensation, Organizational Climate and Motivation, Motivation influenced most significantly on Employee Organizational Commitment.